2017
DOI: 10.15537/smj.2017.4.16409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of apical periodontitis and quality of root canal treatment in an adult Saudi population

Abstract: Objectives:To determine the health status of periradicular tissue and the quality of root canal fillings in an adult Saudi population attending dental clinics for the first time.Methods:This cross sectional study was conducted in the dental clinics at King Saud University, Riyadh and other dental centers (Jeddah, Najran, and Albaha City), Kingdom of Saudi Arabia between year 2010 and 2012. Good-quality panoramic radiographs of 926 Saudi subjects (540 males and 386 females)were analyzed based on the gender, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 37 publications
8
34
1
3
Order By: Relevance
“…Only four articles met the inclusion criteria: 2 studies in animals [38,39] and 2 studies in humans [40,41]. Finally, 21 article were included, 10 studies in animals [22][23][24][25][26][27][28][29]38,39], 10 studies in humans [30][31][32][33][34][35][36][37]40,41] and 1 systematic review [11] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only four articles met the inclusion criteria: 2 studies in animals [38,39] and 2 studies in humans [40,41]. Finally, 21 article were included, 10 studies in animals [22][23][24][25][26][27][28][29]38,39], 10 studies in humans [30][31][32][33][34][35][36][37]40,41] and 1 systematic review [11] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The frequency of AP was more significant in patients with long-term DM than in those with short-term DM. Analysis of the levels of evidence in human studies showed 10 articles, classified as the following: 6 cross-sectional studies descriptive type, representing 60% of the articles included [31,33,35,37,40,41]; three prospective studies 30% [30,34,36] and 1 retrospective study 10% [32]. In these studies, 2088 patients were analyzed, in which the n value was highly variable: 1214 patients [30], 291 patients [35], 90 patients [31], 62 patients [32], 83 patients [33], 46 patients [36], 100 patients [40], 80 patients [34], and 122 patients [41].…”
Section: Yesmentioning
confidence: 99%
See 2 more Smart Citations
“…(8,(23)(24)(25)(26)(27)(28) For countries located in the Middle East, only limited information is available. (29,30) To the best of our knowledge, there are few studies evaluating the prevalence of apical periodontitis in root canaltreated teeth in the Iranian population; (31) therefore, the aim of the present descriptive, historical cohort study was to assess the coronal restoration status, root canal filling quality, periapical health condition, and related factors in endodontically treated teeth at the Dental Faculty of Islamic Azad University of Medical Sciences, Tehran, Iran, in 2011-12.…”
Section: Introductionmentioning
confidence: 99%